Growth and Photoacclimation Strategies of Three Zostera Species Along a Vertical Gradient: Implications for Seagrass Zonation Patterns - Park, Sang Rul; Moon, Kyeonglim; Kim, Seung Hyeon; Lee, Kun-Seop (Frontiers in Marine Science, 2021)
Seagrasses typically display vertical zonation patterns in tropical and temperate areas. In East 22 Asia, three Zostera species (Z. japonica, Z. marina and Z. caespitosa) are distributed at 23 different water depths, leading to zonation patterns from intertidal to subtidal zones. The 24 present study aimed to determine whether these patterns could be explained by differences in 25 their physiological responses, morphological traits and meadows architecture caused by depth 26 variations. Intertidal Zostera japonica had the lowest shoot height and blade width and the 27 highest shoot density, while subtidal Z. caespitosa exhibited the largest specific leaf area. 28 Total carotenoid content and the total chlorophyll/total carotenoid ratio were significantly 29 higher in Z. japonica than in Z. marina or Z. caespitosa. The average carbon stable isotope 30 (δ13C) values were significantly less negative in Z. caespitosa than in Z. marina and Z. 31 japonica. The average maximum relative electron transport rate was higher for Z. marina 32 than for Z. japonica and Z. caespitosa, while the maximum quantum yield values were higher 33 for Z caespitosa than for Z. japonica and Z. marina. The non-photochemical quenching (NPQ) 34 of Z. japonica extinguished within 5-min following the rapid light curve, indicating that most 35 of its NPQ was energy-dependent quenching (qE). The rapid light curve (RLC) parameters 36 and leaf relaxation after RLC showed that Z. japonica is a high-light adapted species and Z. 37 caespitosa is a low-light adapted one. Additionally, Z. caespitosa showed the lowest dark 38 respiration values and Z. japonica, the highest, suggesting that Z. caespitosa can survive with 39 low photosynthetic activity. These results suggested that interspecific variations in the 40 morphological and physiological characteristics, photosynthetic pigments and meadows 41 architecture of three Zostera species were associated with vertical zonation patterns and 42 likely explain their patterns.